The effects of ultra-high pressure on the structural, rheological and retrogradation properties of lotus seed starch. (February 2015) - Guo, Zebin; Zeng, Shaoxiao; Zhang, Yi; Lu, Xu; Tian, Yuting; Zheng, Baodong
Abstract: Lotus seed starch in water (15%, w/w) was subjected to ultra-high pressure (UHP, 100–600 MPa) for 30 min. The effects of UHP on the structural, rheological and retrogradation properties of starch were investigated using polarized light microscopy, solid-state 13 C CP/MAS NMR, rheometry, and differential scanning calorimetry. At 600 MPa, there was loss of the polarization cross, but some birefringence remained, indicating gelatinization. The 13 C CP/MAS NMR results revealed a reduction in crystallinity and peak intensity in the crystalline state with increasing pressure. Native and UHP-treated starch pastes exhibited shear-thinning pseudoplastic behavior. Both G ′ and G ″ increased significantly at 100–500 MPa and decreased at 600 MPa, indicating that excessive pressurization weakens gel structures. UHP-treated starch pastes recovered more slowly their original structures under low-high-low shear conditions than native starch. During storage, UHP-treated starch gels had higher Avrami exponent values and lower recrystallization rates compared with native starch, which suggested a lower retrogradation tendency. Graphical abstract: Highlights: Starch granules were physically affected by UHP treatment. UHP (600 MPa for 30 min) resulted in a complete gelatinization of starch. UHP-treated starch had lower retrogradation tendency than native starch. UHP-treated starch pastes were less structured compared to native starch paste.